A Framework for Nonconforming Mixed Finite Element Method for Elliptic Problems in ℝ3. (9th April 2020) - Jo, Gwanghyun; Kim, J. H.
Abstract : In this paper, we suggest a new patch condition for nonconforming mixed finite elements (MFEs) on parallelepiped and provide a framework for the convergence. Also, we introduce a new family of nonconforming MFE space satisfying the new patch condition. The numerical experiments show that the new MFE shows optimal order convergence in H div and L 2 -norm for various problems with discontinuous coefficient case.